Biomechanics in Medicine and Biology Proceedings of the International Conference of the Polish Society of Biomechanics, Zielona Góra, Poland, September 5-7, 2018 - Arkusz, Katarzyna; Będziński, Romuald; Klekiel, Tomasz; Piszczatowski, Szczepan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the "International Conference of the Polish Society of Biomechanics - BIOMECHANICS 2018" held in Zielona Góra, Poland from September 5 to 7, 2018, and discusses recent research on innovations in biomechanics. It includes a collection of selected papers in all key areas of biomechanics, including cellular, molecular, neuro and musculoskeletal biomechanics, as well as sport, clinical and rehabilitation biomechanics. These themes are extremely important in the development of engineering concepts and methods to provide new medical solutions, especially in the context of an ageing population. Presenting the latest technical advances and research methods used in clinical biomechanics, this book is of interest to scientists as well as junior researchers and students of interdisciplinary fields of engineering, medical, and sports sciences. .
Keywords: Computational intelligence; Biomechanics; Biomedical engineering; Artificial intelligence; Computational Intelligence; Biomechanics; Biomedical Engineering and Bioengineering; Artificial Intelligence